Hubungan Modifikasi Kadar Natrium Dialisat dengan Kualitas Hidup yang Diukur dengan SF-36 pada Pasien Hemodialisis Reguler - Siregar, Bangun Tua; Nasution, Syafrizal; Lubis, Abdurrahim R (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction Regular hemodialysis patients frequently showed fluctuation of quality of life influence by several factors such as anaemia, age, body water volume regulation and nutritional status and others. Sodium dialysate concentration can be regulated by manually and automatically through hemodyalisis machine. The aim of this study was to determine correlation between sodium dialysate modification and Quality of life measured by Short form-36 (SF-36) in hemodialysis patients.Methods This is an experimental study with case-control design. We recruited 54 chronic hemodialysis patients in hemodialysis center at Adam Malik hospital. Blood sample for sodium serum were taken and quality of life measurement by SF -36 questionaire before and after sodium dialysate modification was performed to all subjects. Then to evaluate the difference and correlation.Results Positive significant correlation found in modification group between physical and mental dimension score and sodium dialysate modification with r = 0.864 and r = 0.339.Conclusion There was a significant correlation between Sodium dialysate modification and physical and mental health dimension from quality of life measured in by SF-36 in hemodialysis patients.Keywords :Sodium dialysate modification, Quality of life (SF-36),Hemodialysis